PENGEMBANGAN E-BOOKLET TUMBUHAN PAKU EPIFIT DI TEPIAN SUNGAI DESA MAWANGI SEBAGAI BAHAN AJAR SMA KELAS X - Sulistiani Sulistiani; Sri Amintarti (Bioedukasi Jurnal Pendidikan Biologi, 2026)
The lack of digital-based teaching materials and local potential on the Biodiversity material of the fern sub-concept which is considered difficult to understand by students, can be developed into e-booklet teaching materials. This research and development aims to describe the validity, readability, and effectiveness of the developed e-booklet. The research method used is the 4D development model. The research subjects consisted of 3 experts for the suitability and feasibility test, 9 students for the readability test, and 17 students for the effectiveness test. Based on the research results, the developed e-booklet scored 4,22 in the suitability test with very suitable criteria, in the feasibility test it was 4,44 with very feasible criteria, in the readability test it was 85,76% with very good criteria, and 83,10% in the effectiveness test with very effective criteria. Based on these results, the e-booklet is suitable for use in Biolgy learning, especially in the Biodiversity material, sub-concept of ferns (Pteridophyta).Kata kunci: bahan ajar, e-booklet, keanekaragaman hayati, model 4D, paku epifit.